2015
DOI: 10.1176/appi.ajp.2014.14070878
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Predictors of Dementia in Mild Cognitive Impairment: A Systematic Review and Meta-Analysis

Abstract: Objectives: Public health campaigns encouraging early help-seeking have increased rates of Mild Cognitive Impairment (MCI) diagnosis in Western countries, but we know little about how to treat or prognosticate dementia outcomes in persons with MCI. Method: We searched electronic databases and references for longitudinal studies reporting potentially modifiable risk factors for incident dementia after MCI. Two authors independently evaluated study quality using a checklist. We meta-analysed findings from three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
324
2
23

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(367 citation statements)
references
References 100 publications
18
324
2
23
Order By: Relevance
“…All these conditions have been associated independently with increased risk of dementia (73)(74)(75)(76). Therefore, it is possible also that the MD indirectly improves cognitive function by lowering the risk of well-established risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…All these conditions have been associated independently with increased risk of dementia (73)(74)(75)(76). Therefore, it is possible also that the MD indirectly improves cognitive function by lowering the risk of well-established risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…on the other hand, previous community-based studies also reported predictors of MCI progression: older age, less years of schooling, depression, history of diabetes or stroke, african american and Hispanic ethnicity, and lower baseline MMSe score 30 . Recently, the communitybased Shanghai aging Study investigated the progression of cognitive decline in Chinese elderly 31 .…”
Section: Discussionmentioning
confidence: 93%
“…Além disso, o exercício influencia fatores de risco associados à demência, tais como a resistência à insulina, já que este em idosos está associado à redução do metabolismo de glicose no lobo temporal medial 94,95 . Assim, o exercício é capaz de melhorar a sensibilidade à insulina e contribuir potencialmente para a melhora da memória na doença 96 .…”
Section: Exercício E Doenças Neurodegenerativasunclassified